Economic burden of systemic sclerosis: systematic review - D. L. Klabukova; V. S. Krysanova; T. N. Ermolaeva; M. V. Davydovskaya; K. A. Kokushkin (Фармакоэкономика)
Background. Systemic sclerosis (SSc) is a severe orphan disease, one of the systemic pathologies of connective tissue. This disease has a significant negative impact on the patient’s quality of life and has a high mortality rate. Treatment of its various complications imposes a great financial burden on the healthcare system. The difficulties of daily functioning and social adaptation and the overall burden of SSc for patients, as well as their caregivers, also contribute to the economic component of the disease.Aim. To assess the social and economic burden of SSc.Materials and methods. A systematic review was conducted according to the PRISMA guidelines using predefined PICO(S) criteria. The search was carried out in December 2019 using the MeSH terms in the Embase, MEDLINE / PubMed, Cochrane library databases. The publication date range was 10 years. To identify Russian-language studies, an additional search was conducted in eLIBRARY.ru and the Internet network. The evidence levels of the included studies were determined.Results. A total of 934 studies were identified from all databases; 53 publications were selected for eligibility; 9 of which were included in the final review. There were no studies identified to assess the burden of SSc in Russia, so the evaluations were based on foreign studies. The estimates of the annual direct costs per patient with SSc for the past decade were almost similar in different countries: 5 038 Canadian dollars in Canada, 11 607 Australian dollars in Australia, 17 365-22 016 US dollars in the USA, and 1 413-17 300 Euros in Europe (an average of about 8 000 euros). The cost structure was dominated by direct medical costs for hospitalization and drug therapy and indirect costs were mostly associated with the loss of productivity and early retirement. The costs associated with the diffuse cutaneous form of SSc were statistically higher if compared to the costs for the limited form of the disease. Among the clinical manifestations of the disease, lung lesions and gastrointestinal problems made the largest contribution to the economic burden.Conclusion. SSc is associated with significant healthcare resource use compared to the general population. The economic burden of SS has grown significantly in recent years, and this trend is global. At the same time, it is difficult to evaluate the disease costs in Russia due to a lack of information on the patient population.